Downshifting in Cs2NaBiCl6:Er3+: transforming ultraviolet into near infrared radiation. Issue 8 (14th February 2022) - Huang, Anjun; Duan, Chang-Kui; Wong, Ka-Leung; Tanner, Peter A.
Abstract : A striking UV-NIR downshifting occurs in the Cs2 NaBiCl6 :Er 3+ host, and the 4 I13/2 emitting level is populated by at least two channels. Abstract : The outstanding assets of stability and non-toxicity have produced a surge of research interest into lead-free double perovskite halides for photovoltaic and optoelectronic applications. Here we report the near infrared (NIR) downshifting of micron and nanoparticle (NP)-size erbium-doped Cs2 NaBiCl6 under ultraviolet excitation. The 1.54 nm emission of Er 3+ is obtained by the population of the 4 I13/2 level by an internal Er 3+ temperature-dependent cross-relaxation process and also from bismuth energy transfer. The NIR emission can be switched from sharp to broad band by selective excitation. The doped NPs may be dispersed in organic solvents and the emission intensity can be tuned by choice of solvent.